PENGARUH PEMBERIAN BERBAGAI KONSENTRASI ASAM GIBERELAT DAN JENIS MEDIA TANAM TERHADAP PERKECAMBAHAN BENIH ASAM JAWA (Tamarindus indica L.) - Nanda Septasema Putri; Kartina .; Nuniek Hermita (Jurnal Agroekoteknologi, 2018)
This research was aimed to know the effect in various of gibberellic acid (GA3) concentration and kind of growth plant to germination of tamarind seed (Tamarindus indica L.). This research was conducted in Green House of Faculty of Agriculture University of Sultan Ageng Tirtayasa Serang Banten from October until November 2016. The research used a Randomized Completely Design arranged as factorial and consisted of two factors. The first factor was the concentration of Gibberellic Acid  (GA3), consisted of three levels were G0 (without GA3), G1 (concentration of 500 ppm) and G2 (concentration 750 ppm). The second factor was kind of growth plant, consisted of four levels were M1 (ground), M2 (sand), M3 (husk), and M4 (soil+sand 1:1 (v/v)). The treatment combination was repeated 3 replicates. Parameters measured were day of germination, power of germination, maximum growth potential, growth rate, normal sprout, and abnormal sprout. The results showed that immersion without GA3 tend to gave better effect to the parameters of maximum growth potential (100%), normal sprout (99.6%), power of germination (70.8%), and the speed of growth (6.2%) than the immersion with the provision of GA3. Treatment kind of growth plant that M3 (husk) tended better effect to day of germination (7.5 days), power of germination (72.2%) and abnormal sprout (0.11%). There was no interaction between the concentrations of GA3 and the growth plant for all parameters observed. Keywords: Germination, Gibberelic acid, Growth plant, Tamarind